Transformações no espaço urbano: histórias e memórias da vila A de Itaipu e seus entornos 1970/2013 - Souza, Cesar Augusto Fraga de (2015)
This study aims to analyze the changes occurring in the urban landscape of Foz do Iguaçu, and especially in the region of Itaipu´s village and their surroundings, focusing on Vila "A", between the years 1970 and 2013 , and the way people experienced these changes in their memoirs. The city, located in the Triple Frontier of Brazil, Paraguay and Argentina experienced an unimaginable growth for residents who lived there in the early 1970s. Since 1974, with the start of construction of the Itaipu Hydroelectric Power Plant, the city would become a land of opportunity for thousands of people who, believing in the possibility of getting a job in the power plant, came to the city even without steady employment. In addition, forty thousand people came to work at Itaipu, which led the company's need to build housing for these employees. Three kinds of areas were built: "A"," B" and "C", each one for a category of employees. Over the years, new neighborhoods have emerged in these areas, altering the landscape and the memoirs of the city.